Research-action as method for behavior suicide prevention approach in the basic attention: experience report - Kelly de Holanda Silva, Mara Dalila Leandro de Sousa Brito, Fernando José Guedes da Silva Junior (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8esp49-53